Parental Knowledge and Acceptance of Different Treatment Options for Primary Teeth Provided by Dental Practitioners - Al-Batayneh, Ola B.; Al-Khateeb, Hanan O.; Ibrahim, Waiel M.; Khader, Yousef S. (Frontiers in Public Health, 2019)
Background: Parents have an influence on dental treatment options for young children regarding type of care provided. The aim of this study was to assess parents' knowledge and acceptance of different treatment options for primary teeth provided by dental practitioners for their children. Materials and Methods: In this descriptive, cross-sectional study, caregiver/child dyads (n = 476) were recruited from patients at Pediatric Dental Clinics, Jordan University of Science and Technology. The data collection questionnaire to parents included: 1-demographic data 2-parental knowledge and practices regarding child's oral hygiene, caries and caries prevention 3-parental knowledge and acceptance of different treatment options for primary teeth including two given clinical scenarios (ICDAS-5 molar requiring intra-coronal restoration, ICDAS-6 molar requiring pulp therapy and stainless steel crown) with pictures before and after treatment. Afterwards, the child underwent a dental examination to record dmft/DMFT, gingival and plaque indices. Data was analyzed using SPSS, significance was set at P ≤ 0.05. Results: Children's ages were 2–12 years (mean/SD 6.97 ± 2.5); with 255/53.6% males, 221/46.4% females. There were (166) children 2–5 years in primary dentition; (108/166) 65% had ECC, and (n = 62/166) 37.4% had S-ECC, and (310) 6–12 years in mixed dentition; (278/310) 89.7% had caries. Scaling and extraction were the highest known and accepted treatments for primary teeth by parents (35.5 and 30.1%, respectively), while nitrous oxide/oxygen sedation was the least (3.6%). Parental educational level was significant for composite restorations, fluoride gel application and pulp therapy (P = 0.03, 0.02, and 0.03, respectively) and age above 40 for amalgam restorations (P = 0.04). In both scenarios, most parents preferred to leave any care decision in hands of the dentists with no effect of educational level (P > 0.05). There were 81.5% parents who reported that their children's dental status was good, however, 78.4%/42.8% children had an average dmft/DMFT score 5.34/2.32 and mean PI/GI scores 0.88 ± 0.20/0.17 ± 0.23. Conclusion: Parental knowledge and acceptance about dental treatment options for primary dentition was generally low. Parental education and age had an impact on parental knowledge and practices regarding child's oral hygiene, caries and caries prevention, and some treatment options. There was an overrated parental opinion of their child's teeth status despite the high dmft/DMFT and PI.